The favor : a novel - Griffin, Adele (Sourcebooks Landmark, 2023)
"At I'll Have Seconds, a high-end fairytale vintage dress shop in Manhattan, Nora Hammond loves nothing better than pairing a rare find with the perfect client. At home, Nora grapples with the bleaker reality of enormous debt, a tiny apartment, and ever-dwindling hope that she and her husband Jacob will have a family of their own. When socialite Evelyn Elliot charges into Nora's life, the women spark an immediate connection, and Nora is jettisoned into the heady whirl of New York's moneyed elite. As Evelyn's stylist and confidante, Nora needs to learn all new rules of engagement for the uber-wealthy. But it isn't until Evelyn decides her next cause is to carry a baby for Nora, that these rules- and this unlikely friendship-are tested."--